The Associations Between Internalized Racism, Racial Identity, and Psychological Distress. Issue 4 (August 2021) - Willis, Henry A.; Sosoo, Effua E.; Bernard, Donte L.; Neal, Aaron; Neblett, Enrique W.
Internalized racism, or the acceptance of negative stereotypes about one's own racial group, is associated with psychological distress; yet, few studies have explored the longitudinal impact of internalized racism on the psychological well-being of African American emerging adults. Furthermore, racial identity's role as a protective factor in the context of internalized racism remains unclear. This study examined the longitudinal impact of internalized racism on psychological distress (depressive and anxiety symptoms) and the moderating role of racial identity beliefs among 171 African American emerging adults. Full cross-lagged panel models revealed no main effects of internalized racism beliefs on psychological distress. However, several racial identity beliefs moderated the relationship between internalized racism beliefs and changes in psychological distress over a year later. Initial levels of alteration of physical appearance, internalization of negative stereotypes, and hair change internalized racism beliefs were related to subsequent psychological distress, but only for those with certain levels of racial centrality, private regard, public regard, and assimilationist, humanist, and nationalist ideology beliefs. These findings suggest that, over time, internalized racism and racial identity beliefs can combine to influence the psychological well-being of African American emerging adults.